The business of aerospace : industry dynamics, corporate strategies, innovation models and...the big(ger) picture - Gélain, Antoine (American Institute of Aeronautics and Astronautics, Inc., 2021)
"The Business of Aerospace is a compilation of many of Antoine Gélain's writings for Aviation Week & Space Technology published throughout the last decade. Organized by themes and complemented by brief commentaries introducing underlying business concepts or additional information, these reader-friendly columns are personal viewpoints that bring a fresh and insightful perspective on the aerospace industry. They draw on the author's unique combination of functional expertise (studying and advising on corporate strategy) and industry expertise (working in and with the aerospace industry). Collectively, they cover a broad enough range of issues to provide a comprehensive, 360-degree view of the key themes relevant to the business of aerospace today"-- Provided by publisher.
Includes index.
Keywords: Aerospace industries -- Management.; elektronické knihy; electronic books